Biobased industrial products : priorities for research and commercialization (National Academy Press, 2000)
Petroleum-based industrial products have gradually replaced products derived from biological materials. However, biologically based products are making a comeback--because of a threefold increase in farm productivity and new technologies. Biobased Industrial Products envisions a biobased industrial future, where starch will be used to make biopolymers and vegetable oils will become a routine component in lubricants and detergents. Biobased Industrial Products overviews the U.S. land resources available for agricultural production, summarizes plant materials currently produced, and describes prospects for increasing varieties and yields. The committee discusses the concept of the biorefinery and outlines proven and potential thermal, mechanical, and chemical technologies for conversion of natural resources to industrial applications. The committee also illustrates the developmental dynamics of biobased products through existing examples, as well as products still on the drawing board, and it identifies priorities for research and development.
Title from PDF title page.
Keywords: Biotechnology -- United States -- Forecasting.; Biotechnology -- Government policy -- United States.; Industries.; Green Chemistry Technology; Industry; United States; Biotechnologie -- États-Unis -- Prévision.; Biotechnologie -- Politique gouvernementale -- États-Unis.; Industrie.; BUSINESS & ECONOMICS -- Industries -- Service.; Industries; Biotechnology -- Forecasting; Biotechnology -- Government policy; Biotechnologie.; Biomassa.; Marktontwikkeling.; Plantaardige stoffen.; Grondstoffen.; Agro-industrie.; Procestechnologie.; Vercommercialisering.